0357 Interdisciplinary Training in Pediatric Sleep. (25th May 2022) - Moore, Melisa; Afolabi-Brown, Olufunke; Tapia, Ignacio; Beck, Suzanne; Xanthopoulos, Melissa; Mindell, Jodi
Abstract: Introduction: Sleep is a critical domain of child functioning. However, clinical psychology programs lack formal sleep education while behavioral sleep instruction is deficient in sleep and pulmonary fellowships. Cross-disciplinary training in pediatric sleep is ideal. This study examined medical and psychology trainee satisfaction with two interdisciplinary experiences: a 1-2 semester clinical rotation for medical fellows and psychology doctoral students and a concentrated annual elective for medical students. The rotation includes 1-2 half-day clinics per week wherein medical sleep fellows and behavioral sleep medicine trainees conduct a sleep interview together and ask specific questions within their discipline. With an attending psychologist and physician, they discuss case conceptualization, differential diagnoses, and possible interventions. The team reviews pertinent findings and collaboratively provides recommendations to the patient. Trainees also participate in weekly didactics presented by psychologists and physicians.The second interdisciplinary training experience, Frontiers, is designed to impact physician learners earlier in their careers. Sleep physicians and psychologists teach an annual week-long sleep elective for medical students. Methods: Evaluations from fellows, psychology trainees, and medical students from the most recent 3 years were analyzed to determine trainee satisfaction with the interdisciplinary rotation and the medical student course. Results: Results of sleep fellow evaluations rated the program as having effective teachers`X=4.67 (0.62) and high educational value `X=4.6 (0.83) on a 5-point Likert scale with 5 being the highest. Similarly, psychology trainees rated the overall rotation experience over the past 3 years on a 4-point Likert scale with 4 being the highest as`X=3.74 (0.43).Medical students who took the Frontiers course also rated the training highly on a 4-point Likert scale with 4 being the highest:`X=3.79 (0.43) in 2021, `X=3.76 (0.75) in 2019, and, `X= 3.73 (0.47) in 2018. The course was not offered in 2020 due to the pandemic. Conclusion: Comprehensive pediatric sleep education and training (both clinical and didactic) is feasible within a single interdisciplinary rotation provided simultaneously to both psychology and medical trainees with high trainee satisfaction. Sleep-related in vivo training and didactics are relevant to physician and psychology training programs and prepare trainees for future work in interdisciplinary care. Support (If Any):